Development of an International Prostate Cancer Outcomes Registry. (15th February 2016) - Evans, Sue M.; Nag, Nupur; Roder, David; Brooks, Andrew; L Millar, Jeremy; Moretti, Kim L; Pryor, David; Skala, Marketa; J. McNeil, John
Abstract : Objectives: To establish a Prostate Cancer Outcomes Registry‐Australia and New Zealand (PCOR‐ANZ) for monitoring outcomes of prostate cancer treatment and care, in a cost‐effective manner. Materials and Methods: Stakeholders were recruited based on their interest, importance in achieving the monitoring and reporting of clinical practice and patient outcomes, and in amalgamation of existing registries. Each participating jurisdiction is responsible for local governance, site recruitment, data collection, and data transfer into the PCOR‐ANZ. To establish each local registry, hospitals and clinicians within a jurisdiction were approached to voluntarily contribute to the registry following relevant ethical approval. Patient contact occurs following notification of prostate cancer through a hospital or pathology report, or from a cancer registry. Patient registration is based on an opt‐out model. The PCOR‐ANZ is a secure web‐based registry adhering to ISO 27001 standards. Based on a standardised minimum data set, information on demographics, diagnosis, treatment, outcomes, and patient reported quality of life, are collected. Results: Eight of nine jurisdictions have agreed to contribute to the PCOR‐ANZ. Each jurisdiction has commenced implementation of necessary infrastructure to support rapid rollout. PCOR‐ANZ has defined a minimum data set for collection, to enable analysis of key quality indicators that will aid in assessing clinical practice and patient focused outcomes. Conclusion: PCOR‐ANZ will provide a useful resource of risk‐adjusted evidence‐based data to clinicians, hospitals, and decision makers on prostate cancer clinical practice.